2020
DOI: 10.1039/d0ra00674b
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Rashba spin splitting in Janus transition-metal dichalcogenide monolayersviacharge doping

Abstract: Two-dimensional (2D) Janus transition-metal dichalcogenides (TMDs) (MXY, M ¼ Mo, W; X, Y ¼ S, Se, Te; X s Y) have desirable energy gaps and high stability in ambient conditions, similar to traditional 2D TMDs with potential applications in electronics. But different from traditional 2D TMDs, 2D Janus TMDs possess intrinsic Rashba spin splitting due to out-of-plane mirror symmetry breaking, with promising applications in spintronics. Here we demonstrate a new and effective way to manipulate the Rashba effect in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 46 publications
3
55
0
Order By: Relevance
“…One layer of the halogen atom X in MX 2 can be replaced by another halogen atom Y, which can form a non-centrosymmetric structure and is referred to as Janus materials with the chemical formula Janus MXY [11,12]. Janus MXY have many unique physical properties that distinguish them from conventional 2D materials, including strong in-plane piezoelectric polarization [13], valley splitting [14], Rashba spin splitting [15,16], and good catalytic properties [17]. In recent years, people have conducted a lot of research on Janus MXY for M = Mo, W and X, Y = S, Se, Te, etc.…”
Section: Introductionmentioning
confidence: 99%
“…One layer of the halogen atom X in MX 2 can be replaced by another halogen atom Y, which can form a non-centrosymmetric structure and is referred to as Janus materials with the chemical formula Janus MXY [11,12]. Janus MXY have many unique physical properties that distinguish them from conventional 2D materials, including strong in-plane piezoelectric polarization [13], valley splitting [14], Rashba spin splitting [15,16], and good catalytic properties [17]. In recent years, people have conducted a lot of research on Janus MXY for M = Mo, W and X, Y = S, Se, Te, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the Rashba effect could be controlled by external strain, EF, and charge doping. [ 30,34–36 ] For instance, in WSeTe, it is observed that a small strain (−2%−2%) can substantially change the Rashba SOC (−50%−50%) by modulating the W–Se interaction. The orbital selective external potential method further revealed that the change of W‐ d z 2 and Se‐ p z orbital overlap played a key role in controlling the Rashba SOC.…”
Section: Recent Progresses Of 2d Janus Tmd Monolayersmentioning
confidence: 99%
“…Other methods can be also used to manipulate the Rashba effect. Chen et al [109] explored by firstprinciples calculations the use of charge doping as a strategy to manipulate the Rashba effect in 2D Janus TMDs. The authors found that electron doping can strengthen the Rashba spin splitting at the valence band maximum (VBM) and conduction band minimum (CBM) of 2D Janus TMDs without constant energy consumption, as required by traditional techniques (electric fields and strain engineering).…”
Section: Rashba Effectsmentioning
confidence: 99%